Re-evaluating riboflavin requirements for laying quails: Implications for productivity and yolk antioxidant function - Osman Olgun; Esra Tuğçe Gül; Gözde Kılınç; Alpönder Yıldız; Ainhoa Sarmiento-García (Poultry Science)
This study evaluated the effects of increasing dietary riboflavin levels on laying performance, egg quality, and yolk antioxidant status in Japanese quails, to reassess current riboflavin requirements. A total of 120 female quails (77 days old) were randomly assigned to five dietary treatments (0, 2, 4, 8, and 12 mg/kg riboflavin supplementation on an as-fed basis), with six replicates of four birds each. The trial lasted 84 days. The basal diet contained 1.56 mg/kg riboflavin. Supplementation with 2 mg/kg riboflavin significantly improved egg production (EP), egg mass (EM), feed intake (FI), and feed conversion ratio (FCR), compared to the control group (P < 0.01). The best FCR was observed at 2 mg/kg, while 12 mg/kg supplementation negatively affected EP and FI (P < 0.01). Shell strength increased with riboflavin levels between 4 and 12 mg/kg (P = 0.043), although shell thickness, ratio, and damaged egg percentage were unaffected (P > 0.05). Internal egg quality, including yolk index, albumen index, and Haugh unit, was significantly improved at 8 and 12 mg/kg riboflavin (P < 0.01). In terms of antioxidant capacity, yolk DPPH radical scavenging activity increased linearly with riboflavin supplementation (P < 0.01), while malondialdehyde (MDA) concentrations decreased, particularly at 12 mg/kg (P = 0.025). These findings suggest that riboflavin plays a role in enhancing redox balance in egg yolk. In conclusion, riboflavin supplementation between 6.50–7.04 mg/kg (total dietary levels: 8.06–8.60 mg/kg) was sufficient to maintain optimal performance and improve internal egg quality and antioxidant status in laying quails, suggesting that current riboflavin recommendations may underestimate physiological needs, particularly under modern production conditions.